Shortwave infrared fluorescence in vivo imaging of nerves for minimizing the risk of intraoperative nerve injury. Issue 42 (18th October 2019) - Xu, Heng; Chen, Jun; Feng, Zhujun; Fu, Kan; Qiao, Yusen; Zhang, Zheng; Wang, Wenjin; Wang, Yueming; Zhang, Jian; Perdanasari, Aurelia Trisliana; Hanasono, Matthew M.; Levin, L. Scott; et al.
Abstract : A novel nerve specific imaging agent based on SWIR QD-based in vivo imaging can markedly minimize the risk of iatrogenic nerve injuries during surgeries by providing real-time and long-time SWIR images of peripheral nerves in specific. Abstract : Here, we present a novel nerve specific imaging agent for preventing intraoperative nerve injuries based on SWIR QD-based in vivo imaging, which not only provides real-time and long-time SWIR images to intraoperatively identify nerves but can also markedly minimize the risk of iatrogenic nerve injuries during surgeries.